Mastalgia Among Women Attending the Outpatient Clinics in Alwahda Teaching Hospital, Derna - Soad Ajroud; Aisha Bojazyah; Mohammed Bohlala (AlQalam Journal of Medical and Applied Sciences, 2024)
Mastalgia, also known as mastodynia or breast pain, is a common symptom in clinical practice, with a prevalence ranging from 50% to 80% among women throughout their lives. While only a minority of women may require treatment, a proper assessment is essential for all patients to rule out underlying breast pathology. Addressing concerns, particularly the fear of harbouring cancer and the impact of severe pain on daily life, is crucial. This cross-sectional study aimed to determine the prevalence of both cyclical and non-cyclical mastalgia, identify underlying risk factors, and assess its impact on women’s quality of life. A total of 580 patients were included in the study and evaluated using a closed-ended questionnaire. Among the 580 women studied, the prevalence of mastalgia was found to be 60%, with 43% experiencing noncyclical mastalgia. The majority of individuals experiencing mastalgia onset fall within the age range of 16-25 (41.7%). Mastalgia was positively correlated with stress (99.2%), a positive family history of mastalgia (22%), average body habitus (47.9%), lack of physical exercise (78.4%), high fat diet (20.8%) and excessive coffee intake (25%), a personal history of chronic illness (48.8%). It showed a weak correlation with other factors such as oral contraceptive pills (2.3%) and a positive family history of breast cancer (14.4%). The pain was primarily focal, unilateral, and of mild to moderate severity. Notably, 75% of cases had not undergone breast cancer screening despite their cancer phobia (64.6%). Improving mastalgia management requires increased awareness among women about its risk factors, reassurance, lifestyle modifications (such as regular exercise), and the use of local analgesics. يعد ألم الثدي، المعروف أيضًا باسم ألم الثدي أو ألم الثدي، أحد الأعراض الشائعة في الممارسة السريرية، ويتراوح معدل انتشاره بين 50٪ إلى 80٪ بين النساء طوال حياتهن، مع كون المتغير الدوري هو السائد. في حين أن أقلية فقط من النساء قد يحتاجن إلى العلاج، إلا أن التقييم المناسب ضروري لجميع المرضى لاستبعاد أمراض الثدي الكامنة. إن معالجة المخاوف، وخاصة الخوف من الإصابة بالسرطان وتأثير الألم الشديد على الحياة اليومية، أمر بالغ الأهمية. تهدف هذه الدراسة المستعرضة إلى تحديد مدى انتشار ألم الثدي الدوري وغير الدوري، وتحديد عوامل الخطر الأساسية، وتقييم تأثيرها على نوعية حياة المرأة. تم تضمين ما مجموعه 580 مريضا في الدراسة وتم تقييمهم باستخدام استبيان مغلق. من بين 580 امرأة تمت دراستها، وجد أن معدل انتشار ألم الثدي هو 60%، مع 43% يعانين من ألم الثدي غير الدوري. غالبية الأفراد الذين يعانون من بداية ألم الثدي يقعون ضمن الفئة العمرية 16-25 (41.7٪). ارتبط ألم الثدي بشكل إيجابي بالإجهاد (99.2%)، والتاريخ العائلي الإيجابي لألم الثدي (22%)، ومتوسط عادة الجسم (47.9%)، وعدم ممارسة الرياضة البدنية (78.4%)، واتباع نظام غذائي غني بالدهون (20.8%) والإفراط في تناول القهوة. (25%)، تاريخ شخصي للإصابة بالأمراض المزمنة (48.8%). وأظهرت علاقة ضعيفة مع عوامل أخرى مثل حبوب منع الحمل عن طريق الفم (2.3٪) وتاريخ عائلي إيجابي لسرطان الثدي (14.4٪). كان الألم في المقام الأول بؤريًا وأحادي الجانب وخفيف إلى متوسط الشدة. ومن الجدير بالذكر أن 75% من الحالات لم تخضع لفحص سرطان الثدي على الرغم من خوفها من السرطان (64.6%). يتطلب تحسين إدارة ألم الثدي زيادة الوعي بين النساء حول عوامل الخطر، والطمأنينة، وتعديلات نمط الحياة (مثل ممارسة التمارين الرياضية بانتظام)، واستخدام المسكنات المحلية